Relevansi Konsep Imago Dei terhadap Tanggung Jawab Ekologis di Era Teknologi Digital - Deon Nehemia Paath; Andreas Nugroho; Yosef Antonius (Veritas Lux Mea (Jurnal Teologi dan Pendidikan Kristen), 2026)
This article aims to analyze the relevance of the concept of Imago Dei as a theological foundation for ecological responsibility in the context of the development of digital technology. This study employs a library research method by examining biblical texts and relevant theological literature. The discussion is situated within the context of a global ecological crisis that has been increasingly exacerbated by the impact of digital technology, particularly through rising energy consumption and the accumulation of electronic waste. The findings indicate that the concept of Imago Dei must be understood holistically through substantial, relational, and functional approaches. Such a holistic understanding affirms humanity’s position as responsible stewards of creation before God, rather than as subjects of anthropocentric domination over nature. In the digital era, the concept of Imago Dei functions as an ethical–theological framework that guides the responsible and sustainable use of technology in the care and preservation of creation.AbstrakArtikel ini bertujuan untuk menganalisis relevansi konsep Imago Dei sebagai landasan teologis bagi tanggung jawab ekologis dalam konteks perkembangan teknologi digital. Penelitian ini menggunakan metode studi pustaka dengan menelaah teks-teks Alkitab serta literatur teologi yang relevan. Kajian ini ditempatkan dalam konteks krisis ekologis global yang semakin diperburuk oleh dampak teknologi digital, antara lain melalui peningkatan konsumsi energi dan akumulasi limbah elektronik. Hasil kajian menunjukkan bahwa konsep Imago Dei perlu dipahami secara holistik melalui pendekatan substansial, relasional, dan fungsional. Pemahaman holistik ini menegaskan posisi manusia sebagai penatalayan ciptaan yang bertanggung jawab di hadapan Allah, bukan sebagai subjek dominasi antroposentris atas alam. Dalam konteks era digital, konsep Imago Dei berfungsi sebagai kerangka etis-teologis yang menuntun penggunaan teknologi secara bertanggung jawab, berorientasi pada keberlanjutan, serta pemeliharaan ciptaan.